2020
DOI: 10.1186/s12865-020-00353-0
|View full text |Cite
|
Sign up to set email alerts
|

Epitherapy and immune checkpoint blockade: using epigenetic reinvigoration of exhausted and dysfunctional T cells to reimburse immunotherapy response

Abstract: Background: Cancer cells subvert natural immunosuppression by upregulating the expression of checkpoint proteins and their ligands. For example, tumor cells expressing programmed death-ligand 1 (PD-L1) induce immune cell tolerance to cancers, thereby facilitating tumor progression. The recent clinical success of immunotherapy, particularly checkpoint blockade, represents a significant advance in cancer therapy. However, many cancers develop resistance to immunotherapies, and the underlying mechanisms and how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The combination of epigenetic therapy and immunotherapy is being intensively investigated, and novel trials will be needed to elucidate this role as adjunctive therapy. Epigenetic inhibitors are able to reverse or overcome immune resistance to immunotherapy treatment through upregulation of chemokine expression, antigen processing and presentation machinery, and immune checkpoint molecules [ 241 ]. As such, the rationale is that the epigenetic modifiers can be used to prime and sensitize T cells to immunotherapy.…”
Section: Epigenetic-based Therapeutic Opportunities In Ccrccmentioning
confidence: 99%
“…The combination of epigenetic therapy and immunotherapy is being intensively investigated, and novel trials will be needed to elucidate this role as adjunctive therapy. Epigenetic inhibitors are able to reverse or overcome immune resistance to immunotherapy treatment through upregulation of chemokine expression, antigen processing and presentation machinery, and immune checkpoint molecules [ 241 ]. As such, the rationale is that the epigenetic modifiers can be used to prime and sensitize T cells to immunotherapy.…”
Section: Epigenetic-based Therapeutic Opportunities In Ccrccmentioning
confidence: 99%
“…As already mentioned, during cancer progression a "cancer immune-editing", based on three different phases, elimination, equilibrium and escape, takes place [20]. In the last phase, T lymphocytes become exhausted or tolerized, due to chronic antigen stimulation and the up-regulation of different inhibitory receptors [90]. The most characterized IC are the co-inhibitory molecules CTLA-4, PD-1 and its ligands PD-L1/2 [91], lymphocyte activating antigen-3 (LAG-3) [92], T-cell immunoglobulin and mucin-domain containing-3 (TIM-3) [93] and T cell immune-receptor with Ig and ITIM domains (TIGIT) [94].…”
Section: Ic As Immunotherapeutic Targets In Pediatric Solid Cancersmentioning
confidence: 99%
“…Even though the administration of immune checkpoint inhibitors described in the previous section have successfully reversed the immunosuppressive mechanism by cancer cells in some cases, however, a substantial number of cases still did not show tumor regression or, at most, only a temporary tumor regression. This persistent immune tolerance is due to the proliferation of dysfunctional to exhaustive T cells within the tumor microenvironment [ 43 , 44 , 45 ]. An in-depth study analyzing the transcriptome of every single immune infiltrating lymphocytes in melanoma samples revealed that majority of CD8+ T cells were indeed lacking a complete cytotoxic gene expression, thus making them dysfunctional [ 43 ].…”
Section: Functional T Cells For Effective Immune Attackmentioning
confidence: 99%